228k views
5 votes
wth/#/test-player 100% e The first step in solving the system of equations x+y = 8 and 3x – 2y = -6 using the substitution method would be: O A. 2x+2y = 16 3x - 2y = -6 B. x=8 - y 3(8 - y) - 2y = -6 C. x = 8 + y 3(8 + y) - 2y = -6 OD. x=8-y 3x - 2 (8 - y) = -6 O E E. -3x – 3y = -24 3x - 2y = -6

User Carherpi
by
6.5k points

1 Answer

4 votes

Given the following equations, x + y = 8 and 3x - 2y = -6. The first step in using the substitution method is:

Isolating x in x + y = 8 and substitute the value of x in 3x - 2y = -6.

We get,

x + y = 8

x = 8 - y

Substitute to 3x - 2y = -6.

3(8 - y) - 2y = -6

The answer is letter B.

x = 8 - y

3(8 - y) - 2y = -6

User Urbycoz
by
6.5k points